Fostering 21st-century skills: a phenomenological study of problem-solving development through coding extracurriculars - Maisyaroh Salsa Maharani; Firman Robiansyah; Susilawati (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
The problem-solving skills of elementary school students are still a major challenge in 21st century education, especially in the digital era. This study aims to analyze the development of students' problem-solving skills through Scratch-based extracurricular coding at SD Islam Al-Azhar 10 Serang. Using a qualitative case study method with 25 students as subjects, data was collected through observation, interviews, and questionnaires, which were analyzed using the interactive model Miles, Huberman, and Saldaña. The results of the study revealed that there is a paradox of implementation, where students are more dominant in the indicators of plan implementation (67%) and evaluation of results (62%), but still low in the indicators of problem identification (51%) and plan preparation (49%). These findings show that extracurricular coding is effective in building students' technical skills and perseverance, but is not optimal in developing conceptual and reflective independence. This study highlights the need for transformation in learning models to optimize the development of algorithmic thinking skills and independent problem solving. A more interactive and student-centered approach is needed to encourage more in-depth high-level thinking skills.